Analysis of the relationship between premature rupture of membranes with delivery method and newborn asphyxia - Nurdin, Azizah; Nurdin, Haizah; ., Rahmayanti; Sari, Mutmainnah (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: As many as 20% of maternal deaths are caused by premature rupture of membranes (PROM). The high rate of PROM is believed to affect newborn asphyxia. In addition, the high rate of cesarean section is one of the reasons or most frequent indications of PROM. Therefore, researchers were interested in knowing how the relationship between PROM and delivery method and newborn asphyxia was. Methods: This study was an analytical study conducted with a cross-sectional approach by taking secondary data from patients through medical records of pregnant women who experienced PROM in January 2020 to July 2021. Results: This study found that the incidence of PROM was more dominant in multiparous women 55.4%, in term pregnancy 79.2%, duration of PROM ≥12 hours 55.4%, have normal leukocyte levels 76.2%, the incidence of asphyxia (mild asphyxia) 90.1% and the rate of cesarean section as much as 24%. The bivariate analysis found a significant relationship between the length of PROM and the method of delivery (p value 0.049) and the duration of PROM with newborn asphyxia (p value 0.040) and there was no significant relationship between maternal leukocyte count and newborn asphyxia (p value 0.444). Conclusions: The longer the duration of PROM with delivery, the greater the chance of infection for the mother and fetus. The length or duration of PROM will have an impact on the method of delivery and increase the likelihood of asphyxia in newborns.